GC-MS analysis, comprehensive biological profiling, molecular docking and ADMET studies of Ficus vasta Forssk. n-hexane extract - Hanan Y. Aati; Abdul Rauf; Jawahir Al-Qatani; Bilal Ahmad Ghalloo; Areej Al-Tweel; Mona Khwery; Huma Rao; Muhammad Sajid-ur-Rehman; Kashif-ur-Rehman Khan (Future Science OA)
Aims Ficus vasta Forssk. is a valuable but relatively less explored medicinal and edible plant. This study focused on analyzing the biochemical properties, molecular docking, and ADMET profiling of its n-hexane extract (NHFV).Materials and Methods Phytochemical screening was performed using GC-MS and total bioactive content assays (TPC, TFC, and TTC). Antioxidant potential (NOS and TAC), antiurease, antityrosinase, and hemolytic activities were also assayed. Molecular docking was performed for GC-MS identified ligands against urease and tyrosinase. ADMET investigation was performed to assess drug-likeness and safety profiles.Results NHFV showed significant concentration of TPC (48.01 ± 0.73 mg GA.Eq.g−1), TFC (65.33 ± 0.67 mg QU.Eq.g−1), and TTC (3.45 ± 0.31 mg TA.Eq.g−1). GC-MS analysis identified 43 phytochemicals. Antioxidant assays revealed 91.34 ± 0.86 mg AA.Eq.g−1 NOS and 72.90 ± 0.10 mg AA.Eq.g−1 TAC activity. The extract showed 4.64 ± 0.08% hemolysis, 60.20 ± 1.39% urease, and 75.61 ± 0.64% tyrosinase inhibition. Docking results revealed Cycloartenol (−8.2 kcal/mol) and Lupeol acetate (−8.3 kcal/mol) as potent inhibitors, surpassing standard agents.Conclusion NHFV possesses prominent antioxidant, antiulcer, and skin-whitening potential. Molecular docking and ADMET data support its therapeutic relevance and potential for future drug design.